Mutu Produksi Biji Tanaman Kedelai (Glicine max L.) Dengan Pemberian Bokashi Serta Penyiraman Turunan Em-4 - Dastar Saro (Universitas Tadulako, 2007)
The experiement was carried out in Wisolo vilage, Dolo Selatan, Donggala , Sulteng, Started from January 2007 to April 2007. The purpose of the experiement was to find an optimal dose of fertilization bokashi and sprinkler of generation EM-4 to producing a good Physiological quality of soybean seed. Used seed was Willis variety the experiement and used a randomized block design with dose of fertilization bokashi and sprinkler of generatin EM-4 as the treatment. The treatment was consisted of : (a). A0P0 (Without bokashi + Without generation EM-4/ha), (b).A0P1 (Without Bokashi + Generation EM4 50 ltr/ha), (c). A0P2 (Without Bokashi + Generation EM-4 100 ltr/ha), (d). A1P0 (Bokashi 500 kg + Without Generation EM-4/ha), (e). A1P1 (Bokashi 500 kg + Generation EM-4 50ltr/ha), (f). A1P2 (Bokashi 500 kg + Generation EM-4 100 ltr/ha), (g). A2P0 (Bokashi 1000 kg + without generation EM-4), (h). A2P1 (Bokashi 1000 kg + generation EM-4 50 ltr/ha), (i). A2P2 (Bokashi 1000 kg + generation EM-4 100 ltr/ha). Result indicated that treatment with fertilization bokashi equal to 1000 kg/ha + generation EM-4 100 ltr/ha (A2P2), was produced the highest yield of dry seed and bernas seed.